Evaluating democracy assistance - Kumar, Krishna
With the international community providing billions of dollars each year to promote democratic institutions/cultures in transitional and developing countries, rigorous evaluations have become essential for determining the effectiveness, as well as the future direction, of democracy assistance programs. Krishna Kumar provides a unique, practical guide to the on-the-ground tasks of evaluating and monitoring these programs, from planning to implementation to preparing and presenting evaluation reports. Kumar assesses virtually all of the evaluation and monitoring approaches currently in play, pointing out the strengths and weaknesses of each and suggesting alternative approaches where appropriate. Packed with valuable insights, his book will serve as an essential tool for those who are involved in democracy assistance programming and evaluation, fund it, or simply want to learn more about it